USING INTEGRATED REPORTS TO INCREASE THE RELIABILITY OF FINANCIAL STATEMENTS AND THEIR ROLE IN ENHANCING TAX EXAMINATION PROCEDURES - Anwar Hashem Abboud (Scholars Digest Publishing, 2024)
Integrated reports aim to disclose the company’s vision and mission and display data on environmental, social, governance and economic performance. Financial reports are based on unifying the various reports and presenting them to stakeholders in an understandable way. They enhance and confirm what is stated in the detailed reports and have an important role that increases the reliability of the financial reports. They are useful in the tax examination process to determine taxable income, as the study aimed to demonstrate the importance of integrated reports in enhancing tax examination procedures. The most important finding of the study is that the development in the preparation of reports requires development in the work of the tax examiner and the development of tax examination procedures because the integrated reports provide an accurate presentation of information and increased confidence in them, which leads to reducing the effort on the tax examiner and enabling him to trust the information contained in these reports. The most important recommendations are that the research sample agreed that there is a moral effect of integrated reports in enhancing tax examination procedures. Therefore, we recommend the necessity of relying on the information contained in the integrated reports and increasing confidence in the reports submitted by companies, as they are submitted to different parties and always seek to provide information in a way that increases the value of the company.
Keywords: integrated reports, financial reports, tax examination.